Knowledge, Behavior and Attitude towards Sexually Transmitted Infections and Acquired Immunodeficiency Syndrome of Adolescent Students - Gupta, S; Khanal, T R; Gupta, N; Thakur, A; Khatri, R; Suwal, A; Seomangal, K (Journal of Nepal Health Research Council, 2011)
Background: Adolescence is a period of great physical, mental and emotional turmoil within teenagers. The objective of the study was to assess the knowledge of, attitude to and behaviour towards STI and AIDS among adolescence.Methods: Four randomly selected higher secondary school from students of class XI and XII were included after taking their verbal consent. A pre-designed and pre-tested questionnaire was given to all the participants of the school. In order to get correct answers, specific questions were explained to the students with the help of their class teachers.Results: The results were encouraging with the majority (94.16%) have heard about STIs and HIV/AIDS. Teachers(100%), Newspaper/magazine (90%) and Television (78.33%) were the main informational source about disease. Respondents correctly identified that unsafe sexual contact (86.66%) as major mode of transmission of AIDS andmore than 90% of students regarded the use of condoms as the true preventive method for the disease. Among thoserespondents 6% were sexually active and their partners were either sex worker (71%) or friends (29%).Conclusions: The student’s attitude towards disease was positive and most of the adolescent wished inclusion of sexeducation in their text book from secondary level school’s curriculum.Keywords: acquired immunodeficiency syndrome, adolescent, sexually transmitted infection